Porous carbon nanosheets: Synthetic strategies and electrochemical energy related applications - He, Yafei; Zhuang, Xiaodong; Lei, Chaojun; Lei, Lecheng; Hou, Yang; Mai, Yiyong; Feng, Xinliang (Nano Today, 2019)
Development of two-dimensional (2D) porous carbon nanosheets (PCNs) with an interlinked hierarchical porous structure has attracted great attention due to their synergetic features combining both 2D materials and porous architectures. In recent years, rapid development of synthetic methods for the fabrication of PCNs with hierarchical porous structure, high specific surface area, controlled heteroatom doping, and excellent electrical conductivity has shown signifcant potential in energy-related applications. This review article comprehensively summarizes the recent developments in synthetic methods, including the hard template strategy, soft template strategy, and template-free strategy for successful preparation of PCNs. Three representative electrochemical applications of such PCNs materials for lithium ion batteries, supercapacitors, and electrocatalytic oxygen reductions are presented. At the end of this review, the current existing challenges for the controlled synthesis of PCNs with desired properties and future perspectives for developments of new synthesis methods and new electrochemical energy applications are also discussed.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Electrochemical energy device; Porous carbon nanosheet; Precursor; Template; Two-dimensional